Speak - Anderson, Laurie Halse (New York : Farrar Straus Giroux, 1999)
A traumatic event near the end of the summer has a devastating effect on Melinda's freshman year in high school.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
4.8
Young Adult
Keywords: Emotional problems -- Fiction; High schools -- Fiction; Rape -- Fiction; Schools -- Fiction; Emotional problems -- Fiction; High schools -- Fiction; Rape -- Fiction; School stories